Strengthening Financial Planning Competencies among High School Students: A Community Engagement Program at SMA Edu Global Bandung - Dewi, Maya Safira; Soeprajitno, Raden Roro Widya Ningtyas; Fajriati, Novy (Society : Jurnal Pengabdian Masyarakat, 2026)
The rapid growth of digital financial services has increased adolescents’ access to a range of financial products, including digital payments, e-wallets, and buy-now-pay-later services. However, this increased access is not always accompanied by adequate financial planning competencies, which can expose students to poor financial decision-making and consumerist behavior. This community engagement program aimed to strengthen students' financial planning competencies at SMA Edu Global Bandung through financial literacy education, practical budgeting exercises, financial planning workshops, and training in digital financial record-keeping using the Sepran Expense Manager application. The program involved approximately 150 students from Grades X, XI, and XII. Program effectiveness was evaluated using pre-test and post-test assessments administered to students who completed both questionnaires. The results indicate improvements across all financial planning indicators, particularly in understanding personal financial management, budgeting, and saving practices. Students also demonstrated greater awareness of the difference between needs and wants, of controlling impulsive spending, and of utilizing digital tools to support financial management. The findings suggest that combining financial literacy education with experiential learning activities can effectively improve students’ financial planning competencies and promote more responsible financial behavior. The program highlights the importance of integrating practical financial planning education into school-based student development activities to prepare adolescents for increasingly complex digital financial environments.